Karakterisasi Sifat Fisiko-Kimia dan Organoleptik Produk Cookies Tersubstitusi Tepung Suweg (Amorphophallus campanulatus BI) - Arief Rakhman Affandi; M. Khoiron Ferdiansyah (Jurnal Pangan dan Gizi, 2017)
The adding of stabilizer substance into the formula will make some effect on physicochemical characteristic of suweg’s substitute cookies. The aims of this research was to know the influence of suweg’s flour that used as substitute for the wheat four in cookies production and the effect of using different stabilizer substance on physicochemical and organoleptic characteristic of cookies. The experiment design of this research was using completely randomized design with 2 variable combinations,  kind of stabilizer (CMC and Arabic gum) and concentration of suweg flour (based on mass of whole flour that were used). The suweg flour concentration that used on cookies formula are 10%, 20%, and 30%.  Each experiment combination was conducted in 2 replication. Based on ANOVA analysis, the result indicated a significant effect of suweg flour’s concentration for some characteristic. High concentration of suweg flour will increase the water content (2,75 – 7.71%) and texture quality (3677 – 5054 gram force). The organoleptic characteristic showed that increased the concentration of suweg flour will lead to a decrease of the acceptability of some characteristic like taste, odor, and colour. The use of different kind of stabilizer also influencing the organoleptic characteristic but not really significant.Keywords : cookies, suweg, substitution, characteristic